Stratification of populations with skewed distribution - Pumputis, Dalius (Lietuvos matematikos rinkinys, 2021)
The problem of efficient stratification in the case of skewed population is considered. Four stratification methods are examined. A new adjusted geometric stratification method is introduced. This method is compared by simulation with the Dalenius-Hodges cumulative root frequency method, the geometric method proposed by Gunning and Horgan [2], and the power method offered by Plikusas in [6]. The simulation results show that in most cases considered the power method is the most efficient one.
Keywords: stratification; skewed population; power method; adjusted geometric method